If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(13x-5)+(13x-5)=90
We move all terms to the left:
(13x-5)+(13x-5)-(90)=0
We get rid of parentheses
13x+13x-5-5-90=0
We add all the numbers together, and all the variables
26x-100=0
We move all terms containing x to the left, all other terms to the right
26x=100
x=100/26
x=3+11/13
| (13x-5)(13x-5)=90 | | 7+3m=-5+m | | 4(20-x)=12 | | 20(5^x)=120 | | 6x+23(2)=4x+18 | | 3x10=5x-6 | | 4x+18-6x-23=0 | | 84+a=100 | | 2(4y+7)6y=12 | | m+24=41 | | 5a-4=-1(4-3a) | | 15÷8z=7÷30 | | n/7+8=7.3 | | 1/6x+2/6=-2/12 | | 55/11+7x(2+14=) | | 3m-2/3=7 | | 0.5(2x+5)=0.75(x+1)+2.5 | | x+7.9=13 | | 3(6=3a)-a=-2(9-4a) | | 85+35(2x)+x=360 | | 8x+((1-4x)/8))=7 | | x+x2+5=62 | | 2.6=-5.2(x+3.4) | | 8x+(1-4x)/8)=7 | | 4x/2=2x | | 3x+9=-3+6x | | (2x=7)^=25 | | -m/6=3/7 | | 5^3-2x=5x | | (3x+2)=990 | | 6r=34 | | -7(z-6)=1.2 |